Communicative Type of Right Understanding: A Critical Analysis - Kozhevnikov, Vladimir Valentinovich (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article discusses the main provisions of the communicative theory of law by A.V. Polyakov, which defines legal communication as a legal interaction of subjects that arises on the basis of the social interpretation of legal texts that provide them with correlative powers and legal obligations that are implemented in legal behavior. The paper presents a number of critical remarks regarding this theory of law.